Kemampuan Pemecahan Masalah dan Kemampuan Komunikasi Matematika Siswa - Ihwan Zulkarnain (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2015)
This research is aimed to analyze the influence of cooperative learning model toward the ability of problem solving in Mathematics and students’ ability in Mathematics communication. This research uses experiment method. Data analysis uses MANOVA (Multivariate Analysis of Variants). Result shows that: there is influence of cooperative learning model to the ability of Mathematics problem solving and the ability of Mathematics communication multivariately. This shows that there is difference between matrices of ability of Mathematics problem solving and Mathematics communication to the given cooperative learning model type STAD (Student Team Achievement Division) and type TPS (think, pair, share). (2) by univariate, the result shows: (a) there is no difference in the ability of Mathematics problem solving to those who were given cooperative learning model type STAD and type TPS. This indicates the influence cooperative learning model to the ability of students’ Mathematics problem solving. (b) there is difference in terms of students’ ability of Mathematics communication to who were given cooperative learning model type STAD with type TPS. This shows that there is an influence of cooperative learning model to the ability of Mathematics communication. Keywords: Problem Solving, Mathematics Communication, Learning Model, STAD, TPS.